Modelling Behaviour Design Modelling Symposium 2015 - Thomsen, Mette Ramsgaard; Tamke, Martin; Gengnagel, Christoph; Faircloth, Billie; Scheurer, Fabian (Springer International Publishing : Imprint: Springer, 2015)
This book reflects and expands on the current trend in the building industry to understand, simulate and ultimately design buildings by taking into consideration the interlinked elements and forces that act on them. This approach overcomes the traditional, exclusive focus on building tasks, while posing new challenges in all areas of the industry from material and structural to the urban scale. Contributions from invited experts, papers and case studies provide the reader with a comprehensive overview of the field, as well as perspectives from related disciplines, such as computer science. The chapter authors were invited speakers at the 5th Symposium "Modelling Behaviour", which took place at the CITA in Copenhagen in September 2015.